An outbreak of listeriosis linked to turkey meat products in the Czech Republic, 2012-2016 - Gelbíčová, T; Zobaníková, M; Tomáštíková, Z; Van Walle, I; Ruppitsch, W; Karpíšková, R (Epidemiology and infection, 2018)
Since 2012-2016 an increased number of listeriosis cases, especially from one region of the Czech Republic, were observed. Most of them were caused by strains of serotype 1/2a, clonal complex 8, indistinguishable by pulsed-field gel electrophoresis. Twenty-six human cases were reported, including two neonatal cases in twins. Three cases were fatal. The typing of Listeria monocytogenes isolates from food enabled to confirm a turkey meat delicatessen as the vehicle of infection for this local outbreak in the Moravian-Silesian Region. The food strains belonging to identical pulsotype were isolated from ready-to-eat turkey meat products packaged by the same producer between 2012 and 2016. This fact confirms that the described L. monocytogenes outbreak strain probably persisted in the environment of the aforementioned food-processing plant over several years. Whole-genome sequencing confirmed a very close relationship (zero to seven different alleles) between isolates from humans, foods and swabs from the environment of the food-processing plant under investigation.
Keywords: multilokusová sekvenční typizace; Whole Genome Sequencing; dítě; sérotypizace; Restriction Mapping; Česká republika; Listeria monocytogenes; Aged; Adolescent; restrikční mapování; zvířata; Multilocus Sequence Typing; lidé středního věku; multiplexová polymerázová řetězová reakce; senioři; předškolní dítě; Animals; lidé; Adult; Incidence; Czech Republic; Middle Aged; whole-genome sequencing; dospělí; listeriové infekce; molecular epidemiology; kojenec; Female; Serotyping; krocani; masné výrobky; sekvenování celého genomu; Turkeys; Male; ženské pohlaví; Listeriosis; Agglutination Tests; mladý dospělý; Child; Humans; epidemický výskyt choroby; mužské pohlaví; Young Adult; Disease Outbreaks; Multiplex Polymerase Chain Reaction; Infant; aglutinační testy; incidence; Child, Preschool; Meat Products; mladiství